Performance Analysis Cryptography Using AES-128 and Key Encryption Based on MD5 - Reza Arista Pratama; Eko Hari Rachmawanto; Candra Irawan; Lalang Erawan; Deddy Award Widya Laksana; Rabei Raad Ali (Jurnal Masyarakat Informatika, 2025)
The rampant misuse of data theft has created data security techniques in cryptography. Cryptography has several algorithms that are very strong and difficult to crack, including the AES (Advanced Encryption Standard) algorithm consisting of 128 bits, 192 bits, and 256 bits which have been proven resistant to conventional linear analysis attacks and differential attacks, then there is the MD-5 algorithm (Message-Digest algorithm 5) which is a one-way hash function by changing data with a long size and inserting certain data in it to be recovered. If the two are combined, it becomes more difficult to crack; therefore, to determine its performance, this study conducted a combination experiment of AES-128 with a key encrypted by MD-5, including avalanche effect tests, encryption and decryption execution times, and entropy values of encryption. The types of documents for testing are files with the extensions .docx, .txt, .pptx, .pdf, and .xlsx. After conducting tests on document files obtained from the processing time test, it shows that .txt and .pptx documents dominate with a fast process, while the longest process is obtained by .xlsx and .docx documents for all test files, then the avalanche effect test with an average of 98% and the entropy test is classified as good between values 3 - 7 which are close to value 8. This proves that the combination of the AES-128 algorithm with the MD-5 key can be used as an alternative for securing documents with stronger security, while maintaining standard processing times